1982
DOI: 10.1002/bs.3830270305
|View full text |Cite
|
Sign up to set email alerts
|

Moderator regression and the cusp catastrophe: Application of two-stage personnel selection, training, therapy, and policy evaluation

Abstract: This article demonstrates the applicability of the cusp catastrophe model to a twostage validity study for personnel selection which can simultaneously assess the success of a training program. Personnel selection is of interest substantively since its literature spans psychology, education, economics, management science, political philosophy, statistics, and psychometric theory. The basic problem is, in turn, pertinent to the study of any individuals integrating into an organization, or a therapy or social pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 62 publications
0
69
0
1
Order By: Relevance
“…Cobb (1978Cobb ( , 1980Cobb, Koppstein, & Chen, 1983;Cobb & Watson, 1980;Cobb & Zacks, 1985) tried to solve this problem by developing stochastic catastrophe theory. Other approaches to catastrophe modeling (Guastello's, 1982(Guastello's, , 1992Oliva, Desarbo, Day, & Jedidi's, 1987, GEMCAT technique) have met with some criticism (Alexander, Herbert, Deshon, & Hanges, 1992;Hartelman, van der Maas, & Molenaar, 1998). Cobb showed that, by using stochastic differential equations, there is a cusp family of probability density functions.…”
Section: Catastrophe Theorymentioning
confidence: 99%
“…Cobb (1978Cobb ( , 1980Cobb, Koppstein, & Chen, 1983;Cobb & Watson, 1980;Cobb & Zacks, 1985) tried to solve this problem by developing stochastic catastrophe theory. Other approaches to catastrophe modeling (Guastello's, 1982(Guastello's, , 1992Oliva, Desarbo, Day, & Jedidi's, 1987, GEMCAT technique) have met with some criticism (Alexander, Herbert, Deshon, & Hanges, 1992;Hartelman, van der Maas, & Molenaar, 1998). Cobb showed that, by using stochastic differential equations, there is a cusp family of probability density functions.…”
Section: Catastrophe Theorymentioning
confidence: 99%
“…Catastrophe theory (Thom, 1975;Zeeman, 1977) can offer an appealing approximation for understanding these dynamical changes (Ceja and Navarro, 2011). It has provided successful approximations for other organizational processes, such as work motivation (e.g., Guastello, 1987), employee turnover (e.g., Sheridan, 1985;Sheridan and Abelson, 1983), decision making (e.g., Wright, 1983), personnel selection (e.g., Guastello, 1982), organizational change (e.g., Bigelow, 1982), and competitive dynamics (e.g., Kauffman and Oliva, 1994). However, scholars have not yet tested such models directly in work/health relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic formulations of catastrophe theory have been found, and statistical methods have been developed that allow quantitative comparison of catastrophe models with data (Cobb and Ragade 1978;Cobb and Watson 1980;Cobb 1981;Cobb et al 1983;Guastello 1982;Oliva, Desarbo, Day, and Jedidi 1987;Lange, Oliva, and McDade 2000;Wagenmakers, Molenaar, Grasman, Hartelman, and van der Maas 2005a;Guastello 1992). Of these methods, the maximum likelihood approach of Cobb and Watson (1980); Cobb et al (1983) is arguably most appealing for reasons that we discuss in the Appendix A.…”
mentioning
confidence: 99%